Harmonisation of the Vilnius urban development: Problems and trends of actions - Juškevičius, Pranciškus (Journal of Business Economics and Management, 2003)
The article provides the analysis of the evolution of the planning principals and physical development of the City since 1988 when the state determined planning was mandatory, covering the period since the adoption of the Law on Territorial Planning up to the present date when the City operates in the market economy conditions. The controversy of the City planning and development is pointed out, as well as the necessity to liberalise and harmonise the process. First Published Online: 14 Oct 2010